FONEM SEGMENTAL BAHASA MELAYU RIAU DIALEK PEMATANG SELUNAK INDRAGIRI HULU - Delviza Yuliandari; Auzar '; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT:This study discusses the segmental phonemes of Riau Malay dialect Pematang Selunak Indragiri Hulu. This descriptive research used qualitative approach which aimed to describe the uniqueness of phonemes Riau Malay dialect of Pematang Selunak Indragiri Hulu. This research included into oral data which 8 native speakers of dialect Pematang Selunak the age of 20-60 years old as the informants. The data obtained by interview, record, and stories, then be classified according to the aspects studied. Based on the results of research, Riau Malay dialect of Pematang Selunak Indragiri Hulu has thirty segmental phonemes, that are, /a/, /i/, /u/, /e/, /ε/, /o, /b/, /c/, /d/, /g/ /h/, /j/, /k/, /l/, /m/, /n/, /s/, /p/, /r/, /t/, /y/, /w/, /z/, /R/, /?/, /ñ/, /ɳ/, /ay/, /aw/, and /uy/. The result of this research is a form of documentation of uniqueness phonemes contained in Riau Malay dialect Pematang Selunak Indragiri Hulu.Keywords: Segmental phonemes and Pematang Selunak dialect